Observation of the χc2(2P) meson in the reaction γγ→DD[bar] at BABAR - Aubert, Bernard; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
A search for the Z(3930) resonance in γγ production of the DD[bar] system has been performed using a data sample corresponding to an integrated luminosity of 384 fb−1 recorded by the BABAR experiment at the PEP-II asymmetric-energy electron-positron collider. The DD[bar] invariant mass distribution shows clear evidence of the Z(3930) state with a significance of 5.8σ. We determine mass and width values of (3926.7±2.7±1.1) MeV/c2 and (21.3±6.8±3.6) MeV, respectively. A decay angular analysis provides evidence that the Z(3930) is a tensor state with positive parity and C parity (JPC=2); therefore we identify the Z(3930) state as the χc2(2P) meson. The value of the partial width Γγγ×B(Z(3930)→DD[bar]) is found to be (0.24±0.05±0.04) keV.